Alberto Giordano. Una posibilidad de vida. Escrituras íntimas. Rosario, Beatriz Viterbo Editora, 2023 [2006]. 252 pp. - Fumis, Daniela (Badebec, 2024)
Reseña sobre Alberto Giordano. Una posibilidad de vida. Escrituras íntimas. Rosario, Beatriz Viterbo Editora, 2023 [2006]. 252 pp.